Not Only Parandowski: The Icarus Myth Adapted And Modified for Children in People’s Poland - Pszczolińska, Marta (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2025)
The article offers an overview of adaptations of the Icarus myth aimed at child readers in People’s Poland, published either within the official education system, in children’s magazines reinforcing the school curriculum, or in stand-alone illustrated storybooks. These adaptations, interpretations and retellings, both written before and after WW2, while presenting the same mythical tale of the first aviators, employ specific narrative and adaptation strategies to adjust the myth to the age of the audience and to the values promoted by the authors. In the case of pre-war writers, their interpretation had to be adjusted to meet the requirements of communist censorship, with which the post-war writers were necessarily in agreement.